Convert experiences in Lena Winfrey Seder’s and Kristiane Backer’s autobiographies - Abolmasoomi, Mahya; Hasan, Md. Mahmudul (IIUM Press, 2017)
Autobiography documenting religious conversions has reportedly been around since the fourth century. Today this genre has expanded to include writings of various formats and from various faiths. Prominent convert narratives by male Muslims like Malcolm X (The Autobiography of Malcolm X [1965]) and Muhammad Ali (The Greatest: My Own Story [1975]) are now being followed by those by female converts. Convert Muslim women’s autobiographies provide counter-narratives to the pervasive misery memoirs and contain more representative and unbiased insights into Muslims’ religious and cultural practices and how they see the world. Narratives by Muslim converts from the West are especially important as they seek to bridge the cultural gap between the Western and Muslim worlds. Using the Dialogical Self Theory (DST) and the Islamic concept of the self, this book aims to examine self-representation as described in the following two works: Lena Winfrey Seder’s The Metamorphosis of a Muslim: Autobiography of My Conversion (2011) and Kristiane Backer’s From MTV to Mecca: How Islam Inspired my Life (2012). In addition to analyzing their characterization, this study will also look at the authors’ emplotment methods and discuss the significance of both these narrative elements to the autobiographies, as the authors adapt I-positions to speak to a heterogeneous audience.